Starch graft copolymer and polymer gel applied in Bohai oilfield for water plugging and profile control and their mechanisms. Issue 4 (3rd July 2020) - Cao, Weijia; Xie, Kun; Wang, Xiaoyan; Lu, Xiangguo; He, Xin; Xu, Guorui; Li, Xiang
ABSTRACT: Water plugging and profile control are becoming increasingly important in water-flooding oilfields. In this study, the experiments were conducted to determine the microscopic mechanisms and effects of water plugging, profile control, and 'water plugging + profile control'. Initially, the starch graft copolymer and polymer gel used showed only slight changes in viscosity. However, within 12 h, the viscosities exceeded 100, 000 mPa·s, which indicated that the two agents had good plugging effects. When the plugging agent was starch graft copolymer, the oil recovery with water plugging was 2% and 0.8% higher than the values for profile control with polymer gel on a heterogeneous core and parallel core, respectively. The recoveries with the 'water plugging + profile control' combination for the heterogeneous core and parallel core were 25.9% and 25.5%, respectively, which showed the superior enhanced oil recovery. The mechanism research showed that when the reservoir entered the middle and high water-cut development stages, the residual oil was mainly distributed in the middle- and low-permeability layers near the oil well. Thus, water plugging provided a greater increase in oil recovery. Under the actual demands of the Bohai oilfield, it would be better to adopt a combined water plugging and profile control operation.